The evolution of Germany's net foreign asset position - Guido Baldi; Björn Bremer (DIW Economic Bulletin, 2015)
Available data suggest that, between 2006 and 2012, Germany may have suffered losses to the value of more than 20% of annual economic output on its net foreign assets. Were these presumed losses on German net foreign assets coincidental or can they be attributed to deeper causes? Over time, fluctuating asset valuations are nothing unusual, per se. Losses can quickly turn into profits and vice versa. In addition, the available data should be interpreted with some caution. However, this report also shows that there are lessons to be learned from the loss in value on foreign assets. First, losses have been for the most part in portfolio investments, whereas foreign direct investments by German firms (strategic equity investments) have shown reasonable valuation gains since 2006 by international comparison. At the same time, foreign investors have also seen profit on their direct investments in Germany. With hindsight, it might have been a better strategy for German entrepreneurs and investors to either increase domestic investment or make long-term investments abroad. Further, a comparison with investment behavior in the United States (US) suggests that the profitability of German foreign asset placement has been low. Both countries attract capital from abroad for fixed-interest bonds because both Germany and the US profit from the fact that investors see them as "safe havens" and must pay comparatively low interest rates on bonds. However, while companies and private individuals in the US have simultaneously invested abroad in bonds with high value return, this can generally not be said for German investors in recent years. Some of Germany's net losses can even be attributed to foreign investors making valuation gains on their investments in Germany.
Keywords: F21; F34; F41; 330; International Assets and Liabilities; Valuation Effects; InternationalCapital Flows